Optical Imaging Technology: A Useful Tool to Identify Remission in Cushing Disease After Surgery - Afshari, Ali; Keil, Margaret; Lyssikatos, Charalampos; Belyavskaya, Elena; Valdés, Nuria; Chowdhry, Fatima A.; Parsa, Kian; Ardeshirpour, Yasaman; Pursley, Randall; Khare, Siddharth; Kainerstorfer, Jana M.; Chittiboina, Prashant; Lodish, Maya B.; Mazzuchi, Thomas A.; Gandjbakhche, Amir H.; Stratakis, Constantine A. (Hormone and Metabolic Research, 2019)
We recently reported the use of optical imaging technology to quantify facial plethora in endogenous Cushing syndrome (CS). In the present study, we studied a larger cohort of patients with Cushing disease (CD) and examined water content fraction as well as blood volume fraction as bio-optic markers for determining the efficacy of this methodology as a predictor of lasting remission after surgery for CS. We imaged 49 patients before and after transsphenoidal surgery (TSS) for Cushing disease (CD); 22 patients were also seen at 3–6 months, and 13 patients 12 months post-operatively. On all patients, we used multi-spectral imaging (MSI) to evaluate hemodynamic distributions as well as water content at a specific area of the face. We found a decrease in blood volume fraction after vs. before surgical treatment in the tested facial area in 37 of the 40 patients, as determined with biochemical markers (p<0.001). All patients that were followed up for up to 12 months showed the same decrease from preoperative values and they remained in remission from CD. We conclude that MSI can be used for the evaluation of remission from CD, at least in the immediate post-operative period and up to one year after surgery. The use of this technology can supplement biochemical and other testing for the evaluation of the various treatment modalities available for patients with CD.
Keywords: cushing disease; optical imaging technology; bio-optic marker; facial plethora; serum cortisol; water content volume